Biofuels: from a win–win solution to a wicked problem?. Issue 6 (November 2012) - Fast, Stewart; McCormick, Kes
Current and recent struggles encountered in the development of the transport biofuels sector indicate a significant change in the perception of biofuels. Instead of a win–win solution, transport biofuels have become a major planning challenge; in fact, biofuels can be labeled a wicked problem. The planning studies literature offers some tools to interpret this change and guide future actions. First, by assessing recent experiences of biofuels in the EU and USA against the ten characteristics of wicked problems we find biofuels 'fit' the profile of such issues. Second, we observe that differentiated strategies will suit the different challenges facing biofuels development. We argue that without recognition and engagement of multiple perspectives on transport biofuels they will remain a wicked problem and we therefore advocate for strengthened approaches to communication and engagement.